Estudo de prevalência sobre o uso de tabaco em idosos vivendo na comunidade e associação com fatores sócio-demográficos e de saúde física e mental - Marinho, Valeska [UNIFESP] (2006)
Objective: Evaluate the frequency of smoking in elderly people living in urban areas of Rio Grande do Sul, Brazil. Methods: Cross sectional design. A representative sample of 6961 subjects, randomly selected, aged 60 years-old–and-over, living in community, in urban areas, Brazil, was examined to estimate the frequency of smoking tobacco. All subjects completed in person interview. Smoke use was measured by means of a household questionnaire administered by trained interviewers that inquired about current tobacco use, sociodemographic characteristics, physical and mental health self-rated status. Mental health status was evaluated using the Short Psychiatric Evaluation Schedule. Results: The prevalence of tobacco use was 28,9% among men, 13,6% among women and 18,8% for both sex. The use of tobacco was more frequent in men than in women in a proportion of 3:1. Low income (OR = 1,52), schooling years (illiterate) (OR = 1,35), religion not evangelic (OR = 2,17) and absence of exercise practice (OR = 1,21) presented positive and independent association with tobacco use. Presence of pulmonary disease (OR = 1,93) and mental distress (OR = 1,32) and absence of cardiac disease (OR = 1,51), high blood pressure (OR = 1,51) and diabetes (OR = 1,50) were independently associated with an increased chance of current tobacco use. Increasing age (OR = 0,93) and marital status (married) (OR = 0,66) presented independent and negative association with smoking. Two social characteristics interact: religiosity and race. Non-whites and non - evangelic were 2 fold more likely to be a smoker than the others subjects. Conclusion: Factors associated with increased chance of tobacco smoking were: being men, illiterate, with lower income, presence of respiratory disease and presence of mental disease, absence of cardiac disease, absence of high blood pressure and absence of diabetes. Factors associated with a decreased risk of tobacco smoking were: aging, exercise practice, marital status (married) and religiosity (Evangelist).